Wastewater Reuse to Mitigate the Risk of Water Shortages: An Integrated Investment Appraisal - Chamaki, Foroogh Nazari; Jenkins, Hatice; Hashemipour, Majid; Jenkins, Glenn P. P. (Mdpi, 2022)
This paper evaluates the financial and economic costs of reusing wastewater with reverse osmosis (R.O.) purification systems to mitigate the risks of near potable quality water shortages in an urban water system. A distributional analysis is also undertaken to identify those who bear the externalities of the system. A rich data set is available to conduct an ex-post analysis of such a system operating in Cyprus for several years. The levelized financial cost of the R.O. system if it operates at a 75% utilization rate is USD 1.18/m(3), while the levelized economic cost that includes all the externality impacts is USD 1.20/m(3). However, the closeness of these two values hides a large set of externalities that affect different groups in society in disparate ways. The analysis shows that reusing wastewater in conjunction with a system of R.O. is a very effective way to mitigate the risks of water shortages in a more extensive water system. It also highlights the importance of the nature of the electricity system that generates the electricity to power the R.O. plant in determining the ultimate economic cost of reusing wastewater.
Keywords: reused wastewater; reverse osmosis; water shortage risk; levelized cost; economic cost; emission cost; environmental externalities; distributive analysis